Regulation of ENaC trafficking in rat kidney - Frindt, Gustavo (J Gen Physiol, 2016)
The epithelial Na channel (ENaC) forms a pathway for Na(+) reabsorption in the distal nephron, and regulation of these channels is essential for salt homeostasis. In the rat kidney, ENaC subunits reached the plasma membrane in both immature and fully processed forms, the latter defined by either endoglycosidase H–insensitive glycosylation or proteolytic cleavage. Animals adapted to a low-salt diet have increased ENaC surface expression that is specific for the mature forms of the subunit proteins and is similar (three- to fourfold) for α, β, and γENaC. Kidney membranes were fractionated using differential centrifugation, sucrose-gradient separation, and immunoabsorption. Endoplasmic reticulum membranes, isolated using an antibody against calnexin, expressed immature γENaC, and the content decreased with Na depletion. Golgi membranes, isolated with an antibody against the cis-Golgi protein GM130, expressed both immature and processed γENaC; Na depletion increased the content of processed γENaC in this fraction by 3.8-fold. An endosomal compartment isolated using an antibody against Rab11 contained both immature and processed γENaC; the content of processed subunit increased 2.4-fold with Na depletion. Finally, we assessed the content of γENaC in the late endocytic compartments indirectly using urinary exosomes. All of the γENaC in these exosomes was in the fully cleaved form, and its content increased by 4.5-fold with Na depletion. These results imply that stimulation of ENaC surface expression results at least in part from increased rates of formation of fully processed subunits in the Golgi and subsequent trafficking to the apical membrane.